80.3k views
1 vote
Which is one of the solutions to the equation 2x^2 - x - 4 = 0

User Artless
by
5.8k points

1 Answer

4 votes

Answer:


x_(1)=(1+√(33) )/(4)\\x_(2)=(1-√(33) )/(4)

Explanation:

Using quadratic formula


x=\frac{-b+-\sqrt{b^(2)-4*a*c} }{2*a}

we will have two solutions.

2x^2 - x - 4 = 0

So, a=2 b=-1 c=-4, we have:


x_(1)=\frac{+1+\sqrt{-1^(2)-4*2*-4} }{2*2}\\\\x_(2)=\frac{+1-\sqrt{-1^(2)-4*2*-4} }{2*2}

Finally, we have two solutions:


x_(1)=(1+√(33) )/(4)\\\\x_(2)=(1-√(33) )/(4)

User Rhoda
by
5.3k points